Leptospirosis: A Rare Cause of Acute Hepatitis - Wong, Jo Ann (International Journal of Human and Health Sciences (IJHHS), 2021)
Leptospirosis is a zoonotic infection caused by the pathogenic Leptospira interrogans. Humans acquire the infection either through direct contact with the urine of infected animals, commonly rats or indirect contact of contaminated water or soil. It is a rare cause of acute hepatitis in the UK with fewer than 100 reported cases a year and hence diagnosis is commonly delayed. A 51-year-old fit Caucasian gentleman was admitted with a one-week history of painless jaundice, dark urine and pale-coloured stools. This was associated with feeling unwell, anorexia, nausea and intermittent epigastric discomfort. He binges on alcohol on a weekend. He works as a telephone engineer which occasionally exposes him to sewage water. On clinical examination, he was icteric with mild right hypochondriac tenderness. Liver biopsy was performed and histologically it was suggestive of leptospirosis. He was started on a five-day course of intravenous ceftriaxone followed by two days course of oral doxycycline. His IgM leptospirosis result finally came back as positive. Due to the rarity of leptospirosis in the UK, the serological testing of leptospirosis is only performed in the Rare and Imported Pathogens Laboratory in Porton Down, Salisbury leading to a delay in getting the result. The patient underwent an invasive procedure which can be avoided if the leptospirosis serology was ordered early and result available quickly. Fortunately, the patient made a full recovery after two months. Leptospirosis should be considered in an individual with acute hepatitis and a history of exposure to sewage. International Journal of Human and Health Sciences Supplementary Issue-2: 2021 Page: S22